2006
DOI: 10.1038/sj.onc.1209399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hTERT on metal ion-induced genomic instability

Abstract: There is currently a great interest in delayed chromosomal and other damaging effects of low-dose exposure to a variety of pollutants which appear collectively to act through induction of stress-response pathways related to oxidative stress and ageing. These have been studied mostly in the radiation field but evidence is accumulating that the mechanisms can also be triggered by chemicals, especially heavy metals. Humans are exposed to metals, including chromium (Cr) (VI) and vanadium (V) (V), from the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 70 publications
(75 reference statements)
5
18
0
1
Order By: Relevance
“…Gump et al 19 20 showed that lead exposure could cause over-reactive sympathetic nervous systems and increased levels of cortisol, the hallmarkers of physiological stresses, which have been reported to cause telomere length shortening 2. Similar results of telomere length shortening are also observed following exposure to other heavy metal ions, which cause both acute chromosome damage and genomic instability in the progeny of exposed cells 14 15 30…”
Section: Discussionmentioning
confidence: 94%
“…Gump et al 19 20 showed that lead exposure could cause over-reactive sympathetic nervous systems and increased levels of cortisol, the hallmarkers of physiological stresses, which have been reported to cause telomere length shortening 2. Similar results of telomere length shortening are also observed following exposure to other heavy metal ions, which cause both acute chromosome damage and genomic instability in the progeny of exposed cells 14 15 30…”
Section: Discussionmentioning
confidence: 94%
“…The inhalation of Cr(VI) particles is strongly linked to respiratory cancers in the occupational setting [17], and short telomeres are associated with increased risk for lung cancer [18]. The expression of telomerase in human fibroblasts significantly reduces Cr(VI)-induced cellular toxicity and genomic instability, however, Cr(VI) exposure does not significantly alter mean telomere lengths [19], [20]. Whether Cr(VI) impacts the integrity of individual telomeres, or induces telomeric abnormalities is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, premutagenic adducts induce mutations and also promote larger chromosomal abnormalities (deletions and translocations) resulting from the error-prone repair of DSB through a nonhomologous end-joining process. Exposure of human cells to Cr(VI) is known to induce a series of gross chromosomal alterations, particularly in telomerase-negative primary cells (220).…”
Section: Dna Base Damagementioning
confidence: 99%